2008
DOI: 10.1021/la8008859
|View full text |Cite
|
Sign up to set email alerts
|

Templating Route for Mesostructured Calcium Phosphates with Carboxylic Acid- and Amine-Type Surfactants

Abstract: Mesostructured calcium phosphates constructed by ionic frameworks were synthesized using carboxylic acid- and amine-type surfactants in mixed solvent systems of ethanol and water. A lamellar mesostructured calcium phosphate was prepared using palmitic acid as an anionic surfactant, as in the case using n-alkylamines. A wormhole-like mesostructured calcium phosphate can be obtained using dicarboxyl N-lauroyl- l-glutamic acid, whose headgroup is larger than that of palmitic acid. Similar mesostructured product w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…In general, ordered mesoporous pore arrangement and narrow pore distribution are not observed in conventional calcium phosphate [25]. Some studies demonstrated that nanosized Hap has a high surface functional properties, resulting in better cell adhesion and cell-matrix interactions [2,24].…”
Section: Introductionmentioning
confidence: 99%
“…In general, ordered mesoporous pore arrangement and narrow pore distribution are not observed in conventional calcium phosphate [25]. Some studies demonstrated that nanosized Hap has a high surface functional properties, resulting in better cell adhesion and cell-matrix interactions [2,24].…”
Section: Introductionmentioning
confidence: 99%
“…The formation rate of HA is influenced by the content of Ca 2 + ions and phosphorus. [28,29] Recently,s everalm esoporousc alcium phosphates have been reported, [30][31][32] in which ap hase transformation to the most thermodynamically stable HA is promoted. [29,33,34] The formation of HA crystal was confirmed by XRD measurements.…”
mentioning
confidence: 99%
“…Ye et al prepared hollow HA nanospheres and nanotubes using polymeric micelles of P123 and Tween-60 as templates [11]. Mesoporous HP [12] and ordered mesostructured calcium phosphate [13][14][15][16] were also synthesized using surfactants as structure-directing agents.…”
Section: Introductionmentioning
confidence: 99%